The Process of School Administration and the Relationship between Individual and Organizational Needs - Burgar, Bojan (Revija za elementarno izobraževanje, 2011)
The article investigates the importance of individual and organizational needs in relation to the effectiveness of educational establishments in the areas of management and the guidance of schools. The author proves that if more organizational needs are met, then less individual needs come to the forefront. The author argues that there is no balance and no necessary balanced relationship between organizational and individual needs for the effective management and administration of educational organisations. The article shows the status of eleven areas concerning the management and guidance of schools that directly affect the process of school operation and the possibility of balancing individual and organizational needs for the satisfaction of those involved in effectively running an educational organisation.